Time of Apyrexia after Azithromycin Therapy in Uncomplicated Childhood Typhoid Fever - Chanda Shaha, Kartick; Moshiur Shawon, Hasan; Haque, Ahsanul; Taher, Sadnan; Faysal, S M Ashik (Medicine Today, 2025)
Introduction with Objective: The aim of the present study was to assess the time of apyrexia after Azithromycin therapy in uncomplicated childhood Typhoid Fever. Materials and Methods: A cross sectional study was conducted in the Department of pediatrics, Dhaka National Medical College, Dhaka from July 2024 to October 2024. According to selection criteria one hundred subjects were selected with the age ranging from 1-12 years of either sex who was diagnosed as typhoid fever. Widal test positive was included for the study & specific antibiotic Azithromycin was started. Statistical analyses of the results were obtained by using window based computer software devised with Statistical Packages for Social Sciences (SPSS-20.1). Results: Most of the patients (n=51) belong to 6-8 years age group. Young male patients (52%) were more than the young female patients (48%). Majority of the patients (n=39) time of apyrexia after taking antibiotic was 4 days. Almost three fourth patients (75.0%) had nausea after taking antibiotic. Conclusion: Azithromycin is effective in the treatment of childhood typhoid fever. Majority of the patient’s time of apyrexia after taking antibiotic was 4 days. Medicine Today 2025, Vol.37 (2): 241-243